2016
DOI: 10.5334/jime.430
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of MOOCs: Understanding the Provider Perspective

Abstract: Massive Online Open Courses (MOOCs) have become an accepted way to make learning opportunities available at large scale and with low cost to the learner. However, only if these are made accessible will they be able to offer flexibility of learning and benefits to all, irrespective of disability. Experience in providing accessible online learning at distance universities suggests that this can be best achieved through understanding different roles and the options in planning for adjustments to be made. To effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 20 publications
0
30
0
3
Order By: Relevance
“…Look to introduce and utilise comparable survey approaches across platforms  Analyse further sources of data that describe the activity of learners inside the MOOC.  Undertake a qualitative interview study of learners, building on a recent interview study of providers and stakeholders [5], to capture the disabled learners' experiences with MOOCs in depth. This study will be useful to understand in detail the accessibility issues learners may be facing in MOOCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Look to introduce and utilise comparable survey approaches across platforms  Analyse further sources of data that describe the activity of learners inside the MOOC.  Undertake a qualitative interview study of learners, building on a recent interview study of providers and stakeholders [5], to capture the disabled learners' experiences with MOOCs in depth. This study will be useful to understand in detail the accessibility issues learners may be facing in MOOCs.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative study reported in this paper is a part of a wider research programme to investigate the current accessibility of MOOCs, the processes through which this accessibility is achieved, and the potential use of data to improve MOOC accessibility [4,5]. This particular study aims to understand the current expectations of disabled learners when taking part in MOOCs.…”
Section: Research Aims and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While organisations differ, it is to be expected that there are multiple stakeholders who play different roles in achieving accessibility [10,14,22]. A challenge is for feedback comments to reach those who should understand or act on them in the most effective ways.…”
Section: Work To Get the Relevant Feedback To The Right (Groups Of) Pmentioning
confidence: 99%
“…Research has described how responsibility for accessibility in educational institutions is spread across many roles, including disability support staff, technologists, those responsible for creating materials, convening courses, and management [10,22]. For effective practice to occur, responsibility for accessibility should be embedded into institutional cultures [22,24].…”
Section: The Institutional Contextmentioning
confidence: 99%